0274 Effect of aging on sleep architecture including a novel REM Behavior Disorder phenotype in the PS19 mouse model of tauopathy and effect of a dual orexin receptor antagonist. (25th May 2022) - Kam, Korey; Vetter, Kenny; Varga, Andrew
Abstract: Introduction: This project examines changes to sleep micro-architecture with aging in the PS19 (MAPT P301S) model of tauopathy and response to a dual orexin receptor antagonist (DORA-12) in aged PS19 mice. Methods: 24-hour video PSG recordings occurred in 28 PS19 mice and 22 littermate controls at 2-3 months (young) and 10-14 months (old). Results: Spindle density significantly deceased as a function of both advanced age and PS19 genotype without interaction. We observed a significant interaction between age and genotype on slow oscillation (SO) density such that SO density was higher in young PS19 lower in old PS19 mice vs controls without main effects of age or genotype. Phase amplitude coupling of spindles to detected SO events was significantly decreased as a function of age with a trend toward an age/genotype interaction such that the reduction in coupling was greater with aging in PS19 mice vs controls. We observed unexpected dream enactment during REM in 3 of 11 old PS19 but not in young PS19 mice or control mice at any age. Normalized cumulative EMG area during REM sleep, cumulative duration of elevated EMG in REM, and %REM w/o atonia were all significantly increased in mice displaying dream enactment.Old PS19 mice were also video-PSG recorded for 24 hours while receiving 100 mg/kg DORA-12 vs vehicle control orally twice daily. DORA-12 resulted in significant reduction in latency to persistent NREM and REM sleep, and significant increases in spindle density and SO density, without significant difference in spindle-SO coupling. While we did not observe significant differences in dream enactment measures with DORA-12 due to low sample size, all 3 mice with dream enactment displayed decreases in normalized EMG amplitude in REM and %REM with EMG bursts with DORA-12 ranging from 10 to 60%. Conclusion: Given the importance of spindles, SO's, and their coupling on cognitive processes, these observations can motivate further evaluation of DORA's toward such cognitive processes in neurodegenerative models as well as effect of DORA's on RBD phenotypes. Support (If Any):